The Army Paradox: Leader and Follower Education. Issue 167 (24th August 2020) - Thomas, Ted; Berg, Paul
Abstract: The United States Air Force and the Army's Command and General Staff School use case studies to educate students about their responsibilities to exercise moral courage and effective followership in their military units. This chapter examines followership training and education at different levels within the US Army, both in professional military education schools, as well as in doctrine. We contrast the hierarchical relationships of military organizations and cultures with the need to empower and trust followers. We conclude with instructions on applying the methods the military uses to develop effective followers and provide recommendations for further improvement.